PEMANFAATAN MEDIA PEMBELAJARAN APLIKASI EDUCANDY DALAM MENUNJANG PROSES PEMBELAJARAN BAHASA BALI - Ida Ayu Putu Purnami; I Wayan Gede Wisnu; Ni Ketut Sari Adnyani (Jurnal Komunikasi Hukum, 2023)
This study aims to obtain a clear picture of the Balinese language learning process using educandy application media at the school level, and to obtain a clear picture of the benefits of educandy application-based learning media. The method used in analyzing is descriptive qualitative method. The subjects of this study were students of Class X Accounting 2 SMKN 1 Sawan, while the objects of research were: 1)How was the process of learning Balinese language using educandy application media at SMKN 1 Sawan, 2)What were the benefits of educandy application-based learning media in learning to write Balinese in SMK Negeri 1 Sawan. The results obtained are that the application is very useful. The application of the educandy application has a positive influence on the learning process. Teachers become easier to explain learning materials and students are more enthusiastic when learning. The existence of these applications can also improve student learning outcomes.